Survival of Glass Ionomer Restorations in Primary Molar Teeth in a Tertiary Hospital in Chitwan - Adhikari, S; Tamrakar, L; Bhattarai, R; Thapa, V (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: Glass ionomer cement (GIC) is frequently used as a restorative material in dentistry and has been known for its anti-carious property, biocompatibility and good marginal adaptation. The study aims to evaluate the survival of GIC restorations on primary molar teeth of dental patients attending College of Medical Sciences, Chitwan.Methods: A retrospective longitudinal study was conducted among the patients who were treated with, at least one GIC restoration (GC Fuji II/GC Fuji IX GP) in their primary molars during the past three years. Data were collected to assess the demographic variables like gender, economic status and mother’s education; restoration-related variables like no of surfaces involved, type of material used, location of the restoration in oral cavity, and age of restoration and; outcome related variable i.e. survival of restoration (survived / failed). United States Public Health Service (USPHS) criteria was used to determine survival. Data analysis was done using software SPSS version 17. Chi-square tests were carried out to find out the association between dependent and independent variables. Significance level was set at p